PERANCANGAN KAWASAN MUSEUM WASAKA - Husada, Muhammad Adjie Rahaja; Aufa, Naimatul; Mentayani, Ira (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
The Wasaka Museum is one of the cultural heritage buildings in Banjarmasin, but the surrounding area does not support the existence of this cultural heritage building. Therefore, research on the design of the Wasaka museum area aims to design the Wasaka museum area which focuses on conservation in the Wasaka museum area which does not support the existence of the Wasaka High Ridge House. The Maritime Life concept was chosen to be the answer to this problem using the basic theory of regional character formation. Regional design based on the theory of regional character formation will create a museum area environment that not only meets physical needs, but is also able to conserve the existence of the museum by forming the character and characteristics of the area which focuses on the culture and life of the Banjar people.